2003
DOI: 10.1021/ja036499p
|View full text |Cite
|
Sign up to set email alerts
|

β-Elimination of a Phosphonate Group from an Alkoxy Radical:  An Intramolecular Acylation Approach Using an Acylphosphonate as a Carbonyl Group Acceptor

Abstract: On the basis of facile beta-elimination of a phosphonate group from an alkoxy radical, intramolecular acylation reaction has been developed, in which an acylphosphonate is used as an excellent carbonyl group radical acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…This reaction represents the first example of a phosphono iodocyclization onto a C-C triple bond ( Figure 65) Conformationally constrained a-Boc-aminophosphonates (387), (388) (389), (390) and (391) were made via a transition metal catalysed Curtius rearrangement. 184 Arylphosphonic acids (422) have been discovered to react with a variety of alkenes in the presence of Pd(OAc) 2 and Me 3 NO providing Heck-type adducts (423). 171 A two step synthesis of 2-oxo-2-vinyl-1,3,2-dioxaphospholanes and dioxaphosphorinane (392) involves transesterification of diethyl phosphite with selected diols followed by palladium catalysed coupling of the resultant cyclic phosphites (393) with vinyl bromide (Figure 67).…”
Section: Halogenoalkyl and Halogenocycloalkyl Acidsmentioning
confidence: 99%
“…This reaction represents the first example of a phosphono iodocyclization onto a C-C triple bond ( Figure 65) Conformationally constrained a-Boc-aminophosphonates (387), (388) (389), (390) and (391) were made via a transition metal catalysed Curtius rearrangement. 184 Arylphosphonic acids (422) have been discovered to react with a variety of alkenes in the presence of Pd(OAc) 2 and Me 3 NO providing Heck-type adducts (423). 171 A two step synthesis of 2-oxo-2-vinyl-1,3,2-dioxaphospholanes and dioxaphosphorinane (392) involves transesterification of diethyl phosphite with selected diols followed by palladium catalysed coupling of the resultant cyclic phosphites (393) with vinyl bromide (Figure 67).…”
Section: Halogenoalkyl and Halogenocycloalkyl Acidsmentioning
confidence: 99%
“…It has been shown that phosphinyl radical additions are reversible. [18] Radicals derived from phosphinates have been exploited for the preparation of aromatic compounds, [19] and phosphonyl radical eliminations for the synthesis of ketones, [20] although in both cases the systems were significantly biased to favor the elimination pathway. The first case was a rearomatization, and the second involved a highly reactive acyl phosphonate, with restoration of a C=O bond.…”
mentioning
confidence: 99%
“…Among these new carbonyl radical acceptors, the acyl phosphonate stood out in terms of reactivity. 85 Experiments employing the use of iodo alkenyl acyl derivatives…”
Section: Scheme 42 Effect Of Phenylthio-and Phenylseleno-radical Leamentioning
confidence: 99%
“…As mentioned in the first part of this chapter, there are numerous reports pertaining to either ionic and radical synthesis of ketones. [73][74][75][76][77][78][79][80][81][82][83][84][85] In particularly, 1,5diketones are valuable synthetic starters in the synthesis of fused-ring systems which form the carbon backbone of many interesting classes of compounds such as alkaloids, steroids and terpenes. 86 In addition, 1,5-diketones pave an easy route to functionalized pyridines.…”
Section: Proposed Strategy Of Radical-mediated Synthesis Of 15diketomentioning
confidence: 99%
See 1 more Smart Citation